Intraabdominal infection: peritonitis as abdominal sepsis. Principles of intensive therapy (Perioperaciina Medicina, 2023)
Acute disseminated peritonitis is one of such complex, severe and frequent diseases in abdominal surgery. The lethality of this disease does not decrease below 24–35 %, and with the development of septic shock, it is 60–70 %, and in the case of joining SPON, it reaches 80–100 %. “Abdominal sepsis” (AS) is currently defined as an increase in the SOFA score by ≥ 2 points due to an intra-abdominal infection. If the patient requires the use of vasopressors to maintain an average blood pressure of ≥ 65 mm Hg. (despite adequate fluid volume filling) and a serum lactate level ≥ 2 mmol/l, the clinical situation is defined as septic shock. Monitoring of the level of procalcitonin and the level of C-reactive protein, which solves the problems of verification of the bacterial etiology of sepsis, forecasting its course, and the duration of antibacterial therapy, are among the methods of early diagnosis of abdominal sepsis. Microbiological diagnosis of peritonitis as the main form of AS is mandatory. Effective treatment of IAI is early recognition and elimination of the source, lavage of the abdominal cavity, removal of exudate and interdisciplinary treatment with antibiotics in intensive care.
Keywords: intra-abdominal infection; peritonitis; abdominal sepsis; antibiotics